Role of mRNAs and long non‐coding RNAs in regulating the litter size trait in Chuanzhong black goats. Issue 4 (17th February 2020) - Lian, Zhiquan; Zou, Xian; Han, Yinru; Deng, Ming; Sun, Baoli; Guo, Yongqing; Zhou, Lei; Liu, Guangbin; Liu, Dewu; Li, Yaokun
Abstract: Fecundity improvement is one of the most important objectives for goat breeders as it can considerably greatly increase production efficiency. The molecular mechanisms underlying fecundity in goats remain largely unknown. To explore the molecular and genetic mechanisms related to the fecundities and prolificacies in Chuanzhong black goats, we performed high‐throughput RNA sequencing to identify differentially expressed long non‐coding RNAs (lncRNAs) and mRNAs (DElncRNAs and DEmRNAs, respectively) the ovaries of high‐fecundity and low‐fecundity goats; furthermore, we conducted functional annotation analyses to identify pathways of interest. Overall, 1, 353 DEmRNAs and 168 DElncRNAs were identified. Quantitative real‐time PCR (qRT‐PCR) was performed to validate some randomly selected DElncRNAs and DEmRNAs. We found that two DElncRNAs ENSCHIT00000005909 and ENSCHIT00000005910 might positively influence the expression of the corresponding gene IL1R2 (upregulated in high‐fecundity group), exerting co‐regulative effects on the ovarian function, through which litter size might show variations. KEGG pathway analysis indicated that the DEmRNAs SRD5A2, LOC102191297 and LOC102171967 were significantly enriched in steroid hormone biosynthesis—this pathway was related to animal reproduction. To summarize, our findings expand the understanding pertaining to the biological functions of lncRNAs and contribute to the annotation of the goat genome; moreover, they should be helpful for further studying the role of lncRNAs in ovulation and lambing.